Correlation of Weather Factors and Forest Fire Occurence in KPH Bogor, Perum Perhutani Unit III West Java and Banten HUBUNGAN FAKTOR IKLIM DENGAN KEJADIAN KEBAKARAN HUTAN DI KPH BOGOR PERUM PERHUTANI UNIT III JAWA BARAT DAN BANTEN - Lailan Syaufina; Nova Puspitasari (Jurnal Silvikultur Tropika, 2015)
Forest fire is one of the factors affecting environmental-damage that have been occuring frequently in Indonesia for the last two decades. It is a serious problem that, though, it has not been controlled optimally yet. Climatic condition highly affects forest fire occurence, in term of the frequency, magnitude, season, and the effects. Climatic factors including temperature, humidity, precipitation, wind, and air stability directly affect the potential of forest fire occurence through fuel availability and fire spread. This study was conducted to analyze the correlation between climatic factors and forest fire occurence in KPH Bogor. The result shows that the correlation between climatic factors and forest fire could be modelled through regression analysis. The strongest correlation between climatic factors and forest fire occurrence was indicated by monthly rainfall as the factor affected moisture content of forest fuel.Key words: climatic factors, correlation, forest fire, KPH Bogor, rainfall